Indirect self tuning controller based on placement method / Mohd Affandi Shafie - Shafie, Mohd Affandi (1999)
In this thesis the design of an adaptive controller, i.e. self tuning controller based on pole placement method is discussed. The servomotor is assumed to be slowly time varying and its parameters are identified recursively using the recursive least squares estimation technique. The estimated parameters are then used to update the controller setting to obtain the optimum performance. The controller is designed using Ragazzini's Direct Synthesis Method, which is pole-zero cancellation. The controller system is simulated using MATLAB and is shown to perform according to specifications.